Pediatric Head Injuries in Summer Camps. (May 2020) - Kolberg, Kristen; Saleem, Noor; Ambrose, Michael; Cranford, Jim; Almeida, Andrea; Ichesco, Ingrid; Schellpfeffer, Natalie; Hashikawa, Andrew
Summer camps have a unique supervisory environment that may lead to increased head injury risk for children. The epidemiology of head injuries in camps is unclear. We partnered withCampDoc.com to review head injury reports from camp nurses in 2016 from 197 camps in 36 states. A total of 4290 (92%) reports were coded as definite head injuries, 47% (n = 2002) in female campers, with median camper age of 10 years. Head injury severity was coded as mild (94%, n = 4040), moderate (6%, n = 248), or severe (<1%, n = 2). Only 3% (n = 134) were medically evaluated, and 29% (n = 1221) were sports-related. Head injuries were categorized as definite (3%, n = 137) and probable (13%, n = 572) concussions, with 39% (n = 277) being sports-related and 61% (n = 83) of definite concussions incurred by female campers. Summer camps, while an important location of head injury risk, appear to be a safe environment for youth.